Influencia de la aplicación del cuento infantil en el proceso de enseñanza – aprendizaje de los niños y niñas del centro de educación inicial Celia Mora Sares, de la ciudad de Machala, período lectivo 2012 – 2013. - Mera Tello, Jessica Lucrecia (2013)
This research work is based on the study of the influence on the implementation of the children's story in the educational process of the children of the first year of basic education in the garden of infants Celia Mora of Sares of Machala city, where the teacher will facilitate the incorporation of an innovative plan for a solution of problems with regard to the educational process.